PROGRAMMABLE CONTROLLER AND HUMAN-MACHINE INTERFACE RETROFIT FOR SHEET-METAL CUTTING CONTROL - Rick Resa Wahani; Michael Edward Gregerio Kimbal; Moody Noldy Tumembow; Priyono; Herotje Siwi (CV. TOTUS TUUS, 2026)
A 1995 Colgar sheet-metal cutting machine used in the Manufacturing Laboratory of Politeknik Negeri Manado experienced degraded cutting performance, a disabled automatic cycle, an unreliable safety function, and a non-functional blade-gap adjustment mechanism. This study aimed to retrofit the machine control system by integrating a programmable logic controller, a human-machine interface, limit sensors, a variable-frequency drive, and interlock-based emergency logic. The study used a research-and-development design combined with experimental validation. Data were collected through machine inspection, input-output mapping, ladder-diagram programming, HMI screen development, electrical installation, and functional testing with 2 mm and 6 mm steel plates. The retrofit restored manual and automatic blade movement, reactivated the worktable/blade-gap mechanism, enabled operator monitoring through HMI screens, and improved safety through upper and lower limit sensors, emergency stop logic, visual indicators, and audible alarms. Post-retrofit tests showed that the blade-gap setting operated normally, with a 0.35 mm gap for 2 mm steel plates and a 0.75 mm gap for 6 mm steel plates. The machine could perform a complete automatic down-and-up cycle through a single command while retaining full manual control. The findings indicate that PLC-HMI retrofitting is a practical modernization strategy for legacy sheet-metal machines because it improves functionality, operational accuracy, usability, and machine safety without replacing the main mechanical structure.